Transmission of whole-body vibration and its effect on muscle activation - Tankisheva, E.; Jonkers, I.; Boonen, S.; Delecluse, C.; Harry van Lenthe, G.; Druyts, Hans L. J.; Spaepen, P.; Verschueren, S. M. P. (The Journal of Strength and Conditioning Research, 2013)
The aim of current study was to measure the transmission of whole-body vibration through the entire body and to relate this to body posture and induced muscular activation. Eight clinically healthy subjects performed 3 static body postures—high squat (135°), deep squat (110°), and erect stance, whereas vibration transmission was assessed over a wide range of accelerations (from 0.33 to 7.98 g) and frequencies (from 30 to 50 Hz). To assess the vibration transmission, 9 triaxial accelerometers were attached from the ankle up to the head and the root mean square of acceleration signal of each site-specific body point was calculated. Additionally, muscle activity from 7 lower limb muscles was recorded. The results showed a significant attenuation of the platform accelerations transmitted from the feet to the head. Compared with erect stance, knee bent posture significantly diminished vibration transmission at the hip, spine, and the head (p < 0.05). Vibration transmission to the spine was significantly lower in deep vs. high squat (p < 0.05), suggesting that further knee bending may reduce the risk of overloading the spine. Vibration increased the muscle activity in most leg and hip muscles during both squat postures, although, on average, no clear dose-response relationship between the acceleration and/or frequency and muscle response was found. The muscular activation of vastus medialis and rectus femoris showed clear negative correlation to the vibration transmission at the sternum. The specific vibration parameters used in the present study can be considered as safe and suitable for a training program. Moreover, the present results contribute to optimize the most advantageous whole-body vibration protocol and to determine the beneficial effects on muscle and bone.